Src-family kinase–dependent disruption of endothelial barrier function by Plasmodium falciparum merozoite proteins - Gillrie, Mark R. (American Society of Hematology, 2007)
Pulmonary complication in severe Plasmodium falciparum malaria is manifested as a prolonged impairment of gas transfer or the more severe acute respiratory distress syndrome (ARDS). In either clinical presentation, vascular permeability is a major component of the pathologic process. In this report, we examined the effect of clinical P falciparum isolates on barrier function of primary dermal and lung microvascular endothelium in vitro. We showed that parasite sonicates but not intact infected erythrocytes disrupted endothelial barrier function in a Src-family kinase–dependent manner. The abnormalities were manifested both as discontinuous immunofluorescence staining of the junctional proteins ZO-1, claudin 5, and VE-cadherin and the formation of interendothelial gaps in monolayers. These changes were associated with a loss in total protein content of claudin 5 and redistribution of ZO-1 from the cytoskeleton to the membrane and the cytosolic and nuclear fractions. There was minimal evidence of a proinflammatory response or direct cellular cytotoxicity or cell death. The active component in sonicates appeared to be a merozoite-associated protein. Increased permeability was also induced by P falciparum glycophosphatidylinositols (GPIs) and food vacuoles. These results demonstrate that parasite components can alter endothelial barrier function and thus contribute to the pathogenesis of severe falciparum malaria.